Strong sexual size dimorphism in the Dark-eared Myza Myza celebensis, a Sulawesi-endemic honeyeater, with notes on its wing markings and moult - Leishman, Alan J; Harris, J. Burton C; Putra, Dadang Dwi; Prawiradilaga, Dewi M; Noske, Richard A (KUKILA, 2013)
We present morphometric and moult data for the Sulawesi-endemic Dark-eared Myza, based on 35 individuals captured at Lore Lindu National Park, Central Sulawesi, during March–April and July 2011. Four individuals banded in March were recaptured at the study site in July, suggesting that the population is probably sedentary. Like most meliphagids, although this species is not sexually dimorphic in plumage, measurements show that males are significantly heavier and have longer wings, tail and head–bill than females. Seven of the 16 adults in March–April and five of the 19 in July were moulting their primary feathers. Assuming that primary moult follows breeding, estimated laying dates for adults in the final stages of moult suggest breeding in December and early April, the latter corroborated by the presence of brood patches on two females in late March. A brood patch on a female in July further suggests that the breeding season is protracted. All birds photographed also showed distinct buff tips to most, if not all, secondary coverts and buff fringes to median coverts, a feature that appears to have gone unnoticed in the literature.